2013 20th International Packet Video Workshop 2013
DOI: 10.1109/pv.2013.6691439
|View full text |Cite
|
Sign up to set email alerts
|

Circuit Breakers for Multimedia Congestion Control

Abstract: Abstract-Real-time multimedia flows comprise a large, and increasing, fraction of the traffic on the Internet. An important subset of that traffic, primarily due to interactive applications, runs over UDP/IP, and requires applications to implement congestion control to ensure the stability of the network. The IETF is developing congestion control algorithms for such uses as part of the new WebRTC standards, but there is no standard algorithm that can be used at this time. We do not propose a congestion control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Our evaluation of the RTP-CB behaviour contributes to the currently limited experimental assessment of the RTP-CB available in the literature [5]. For sample video sessions (either allowed or terminated by the RTP-CB), we consider the video quality, along with bandwidth usage/share, to assess the effectiveness of the RTP-CB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our evaluation of the RTP-CB behaviour contributes to the currently limited experimental assessment of the RTP-CB available in the literature [5]. For sample video sessions (either allowed or terminated by the RTP-CB), we consider the video quality, along with bandwidth usage/share, to assess the effectiveness of the RTP-CB.…”
Section: Discussionmentioning
confidence: 99%
“…Congestion-controlled RTP flows, and uncontrolled RTP flows in lightly loaded environments, operate without triggering the RTP-CB, while misbehaving flows that cause congestion will be terminated. Evidence in the literature supports the ability of the RTP-CB to prevent persistent severe congestion [5] [6] using the RTP-CB congestion rule of [4]. Alongside this rule, a media usability rule for the RTP-CB has been suggested [4], but to date no algorithm has been proposed to implement it.…”
Section: Introductionmentioning
confidence: 99%
“…We show that simply reducing the multiplier in the congestion circuit breaker is not sufficient to address this issue, but that using the more complete TCP model of Padhye et al gives better performance. Unfortunately, our previous work [10] has shown that this more complete TCP model leads to an overly sensitive circuit breaker when used in residential access networks. We believe some of this over-sensitivity is due to averaging packet loss events over long RTCP reporting intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Performance of the circuit breaker on residential access links and for interactive multimedia is studied in [10]. This shows the circuit breaker takes at least 20 s to engage when the reported loss fraction is higher than 33 %, giving time for a congestion control algorithm to operate.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation